Communication as a socio-psychological dimension of participatory planning processes: cases of the participatory processes of Gazi, Kaymaklı, Odunpazarı and Seyrek in Turkey. Issue 2 (2nd April 2016) - Kulözü, Neslihan
ABSTRACT: This study aims to explore the attributes of communication and their beneficial and/or detrimental effects in the case of the 'Local Government & NGO Cooperation in Participatory Democracy' Project. After that the effects of the communication dimension on contextually different participatory processes will be assessed through comparative assessment processes in Gazi, Kaymaklı, Odunpazarı and Seyrek, as partners in the case project. For this exploratory case study, in-depth interviews were conducted with participants from four localities to obtain subjective descriptions of communication and its effects on their own processes.